The Role of Halal Facilitators in Empowering MSME Products: A Case Studi in Lengkong Subdistrict - Heni Mulyani; Neneng Nurhasanah; Nandang Ihwanudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This paper discusses the role of halal facilitators in strengthening MSME products in Lengkong Subdistrict, Bandung City. Halal certification is a crucial instrument to ensure product permissibility, increase consumer trust, and expand market access. This research employed a qualitative descriptive method with purposive sampling techniques. Informants consisted of halal facilitators, MSME actors, and consumers. The findings reveal that halal facilitators play a significant role in four key areas: consultation, halal literacy, technical assistance, and verification-validation (verval). Each role contributes to improving product quality, halal understanding, and MSME competitiveness. This study highlights the importance of synergy between facilitators and business actors to optimize the benefits of halal certification. The findings also reflect the relevance of integrating maqashid sharia values into halal mentoring practices.